Ocular motor cranial neuropathy and risk of thyroid cancer: A Korean population-based study - Jaeryung Kim; Kyung-Ah Park; Kyungdo Han; Jin-Hyung Jung; Sei Yeul Oh; Soolienah Rhiu (PLoS ONE, 2025)
This study investigates whether ocular motor cranial neuropathy (OMCN) can predict the onset of thyroid cancer given its association with common cardiovascular risk factors including obesity, diabetes mellitus (DM), hypertension, and dyslipidemia. We conducted a retrospective, nationwide, population-based cohort study utilizing data from the Korean National Health Insurance Service. Individuals comprised those aged ≥ 20 years diagnosed with OMCN between 2010 and 2017. Exclusions were based on pre-existing conditions, inability to match controls, or incomplete data. The study involved 118,686 participants, with 19,781 in the OMCN group and 98,905 controls, matched for age and sex. Patients with OMCN showed a significantly higher risk of developing thyroid cancer (hazard ratio [HR] =  1.392 [95% confidence interval, 1.075–1.802]) compared to controls after adjusting for potential confounding factors. This association was more pronounced in participants with DM and women (HR =  2.288 in DM vs. HR =  1.209 in non-DM, p =  0.0450; HR =  1.677 in females vs. HR =  0.824 in males, p =  0.0246). The findings suggest OMCN as a potential early predictor of thyroid cancer risk, particularly in diabetic and female patients. Further research is needed to explore the underlying mechanisms linking cardiovascular risk factors to the relationship between OMCN and thyroid cancer. Proactive management of these risk factors in OMCN patients may contribute to thyroid cancer prevention.